Acomodação dialetal: análise da fricativa coronal /S/ em posição de coda silábica por paraibanos residentes em Recife - Lima, Izete de Souza (2013)
The present study aims to understand the dialectal accommodation process of paraibanos who live in Recife (PE), based on Communication Accommodation Theory (GILES et al., 1987) and in the theoretical-methodological contributions of the Variation Theory (LABOV, 1996; 1972). The phonological phenomenon which will allow us to check the accommodation effects is the realization of coronal fricative /S/ in coda position by the fact that this segment clearly marks the difference between the dialects under study. The corpus was constituted by 9 paraibanos informants residing for at least two years in Recife. The collected data were analyzed quantitatively and qualitatively. The quantitative analysis enabled us to identify statistically the factors that are contributing to the accommodation, while the qualitative analysis enabled us the interpretation of subjective data that contributed to the accommodation of the new dialect or the preservation of the dialect of origin. The statistical treatment realized through Goldvarb X (SANKOFF, TAGLIAMONTE & SMITH, 2005) showed, in increasing order of significance, which the most relevant variables were: permanence time, amount of exposure to dialect, following phonological context, the style and the frequency of visits. The qualitative analysis developed through the participants speech allowed us identify the linguistics attitude of the informants. We realized that positive evaluation influenced the linguistic accommodation even as the negative evaluation led them to preserve their dialect of origin as a way of distancing.